The financial services marketing handbook : tactics and techniques that produce results - Ehrlich, Evelyn, 1950-; Fanelli, Duke, 1954- (Hoboken, N.J. : Bloomberg Press, 2012)
'The financial industry is under intense pressure to improve profits, retain high-value clients, and maintain brand equity--without straining budgets. The Financial Services Marketing Handbook, Second Edition gives sales and marketing professionals the information they need to stretch more value from each marketing dollar.The Second Edition includes updated case studies and charts. This new edition looks at important topics in the industry such as: Real time monitoring of conversations (e.g., Twitter and Facebook) and the impact on branding and positioning; New info on landing pages, e-mail success factors; Behavioral economics to psychology of money and budgeting'--
Series data from the jacket.
Includes bibliographical references and index.
Keywords: Financial services industry -- United States -- Marketing; Financial planners -- Marketing; Customer relations; Financial services industry -- Computer network resources